Interaction of Plant Growth Promoting Rhizobacteria (PGPR) and Endophytes with Medicinal Plants – New Avenues for Phytochemicals - Dhandayuthapani Kandavel, Soundarapandian Sekar* and (Journal of Phytology, 2010)
Plant growth promoting rhizobacteria (PGPR) are usually applied to a wide range of agricultural crops for the purpose of growth enhancement, including increased seed germination, plant weight, and harvest yields. PGPR colonization triggers plant growth by bacterial synthesis of plant hormones including indole-3- acetic acid, cytokinin, and gibberellins as well as by increased mineral and nitrogen availability in the soil. Some of them were also known to protect their host plant from pathogenic microorganisms. The role played by PGPR in relation to medicinal plants and their effect on the production of botanicals is an area remaining naive. This paper brings out the possible PGPR – medicinal plant interactions which could improve the potency of the medicinal plant, particularly the cultivated one. Endophytic microorganisms of medicinal plants and their role in relation to bioactive potentials in the generation of phytochemicals also have been discussed. Key words: Biotization, Endophytes, Medicinal Plants, PGPR, Phytochemicals, Secondary Metabolites <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG"> <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Soundarapandian Sekar and Dhandayuthapani Kandavel. Interaction of Plant Growth Promoting Rhizobacteria (PGPR) and Endophytes with Medicinal Plants – New Avenues for Phytochemicals. J Phytol 2/7 (2010) 91-100.